Os diversos modelos de formação inicial de professores para o ensino primário de Moçambique: permanências e rupturas - Gabriel, Silvio Francisco (2024)
The study investigated the Initial Training of Primary School Teachers in Mozambique, in order to understand how the current training models contribute to the construction of professionalism in teaching. In this context, the need to carry out this research arose, around training in the social recognition of an activity as a profession, determined in the literature on the sociology of professions and education. The research aims to analyze professionality data in several demonstrations that guide FIP in Mozambique, in the initial training models 10th class + 1 year, 10th class + 3 years and 12th class + 3 years. This is a qualitative research based on the description and analysis of documents, the development of the study continued based on questionnaires made to nine (9) trainers, twelve (12) trainees and four (4) managers. The study was based on the possibility of reinforcing the cohesion between discourses and practices constructed in ITE and clarifying the concept of professionality intended in ITE for Primary Education. The results indicated that there is a total lack of harmony between the concepts of professionalism, teaching shown in the different guiding documents, speeches by training agents and the teaching practice of trainers. In relation to the specificities of professionalism, the power of decision-making and innovative researcher stand out as one of the qualities recognized for teachers. However, this aspect contradicts the reality shown, as the lack of power of trainers/teachers over changes to curricula was verified and, despite the existence of some trainers with good qualifications, it was noted that there is a lot of teaching practice aligned with functionalization of what professionalism is